Determination of the real exchange rate: the experience of Barbados - Modeste, Nelson (ISER MonaJA, 1993)
Tests the proposition that a devaluation increases the real exchange rate unless offset by strong growth either in money wages at home or in worker productivity abroad. Sketches a single model of real exchange determination and tests using data from 1974 to 1989.